Five new diterpenoid alkaloids from Aconitum sczukinii Turcz. (February 2022) - Li, Jia-Min; Li, Xiaohuan; Gao, Feng; Cai, Le; Liang, Xiao-Xia; Chen, Lin; Zhou, Xian-Li
Graphical abstract: Highlights: Five new diterpenoid alkaloids were isolated from Aconitum sczukinii Turcz. New compound 1 is the first diterpenoid alkaloid that contains a lactone D ring. A plausible biosynthetic pathway for the formation of 1 is proposed. Abstract: Ten diterpenoid alkaloids, including five new ones, sczukiniline A–E (1 -5 ), were isolated from the root of Aconitum sczukinii. Their structures were elucidated based on the interpretation of spectroscopic data (HRESI-MS, IR, 1D- and 2D-NMR). Among the five new diterpenoid alkaloids, 1 -3 are hetidine-type C20 -diterpenoid alkaloids, while compounds 4 and 5 are lycoctonine-type C19 -diterpenoid alkaloids. Noteworthily, sczukiniline A (1 ) features a novel ester group between C-12 and C-14, forming a D ring containing a lactone structure, resulting in a new skeleton of hetidine-type C20 -diterpenoid alkaloid.